Multi-ethnic Girls' Social Positional Identities in Educational Transitions. Issue 1 (1st March 2020) - Roth, Solveig; Stuedahl, Dagny
Abstract: In this article, we examine the case history of a young multi-ethnic Norwegian girl, whom we call Anna, from the age of 15 to 17 to show how her self-understanding of positionings within her educational transitions illustrates how gendered expectations in a Norwegian context influence girls' future trajectories. We use the concepts of social positional identities in figured worlds and performativity to explore self-understanding. Anna's case history illustrates how gender performativity comes about out of a complex web of family, school, and societal expectations. We discuss the tensions Anna experienced in her educational trajectory and the changes in her performative positioning when she entered upper secondary school. We consider the ways in which this had implications for her future life trajectory and offer suggestions to educators on how to understand and support the different learning trajectories of multi-ethnic students.